Justice in the Allocation of Public Facilities: A Legal-Philosophical Analysis of Rights and Social Interests (A Case Study on the Use of Strobe Lights and Escort Patrols by Government Officials) - Putri, Syifadilla Subagyo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study analyzes the distribution of justice in the use of public facilities through a legal-philosophical approach, focusing on the use of strobe lights and police escorts by government officials. The objective is to evaluate the implementation of justice principles in legal and social contexts, particularly regarding equal public rights. The research employs a normative juridical method through statutory and literature approaches. The findings reveal that the misuse of public facilities by officials outside emergency situations constitutes a violation of social justice and human rights principles. Therefore, consistent and transparent law enforcement is needed to ensure equality and justice in public life.